Age-associated DNA methylation determination of semen by pyrosequencing in Chinese Han population. (December 2017) - Li, Luyao; Song, Feng; Huang, Yun; Zhu, Hong; Hou, Yiping
Abstract: In forensic casework, age-prediction of crime-related biological stains can be of significant importance for the reconstruction of the events at a crime scene. Recently, DNA methylation, the patterns in particular age-related CpGs (AR-CpGs) has emerged as an alternative strategy for forensic age estimation, which was reported as tissue specific and showed variant methylation quantitative in different platforms. Semen, as one of the most common biological traces in forensic sexual crime scene, was firstly reported to estimate age based on 3 CpG sites (cg06304190, cg06979108 and cg12837463) with SNaPshot method by Lee et al. In this study, we aimed to evaluate the cg06979108 as potential age prediction marker in semen in Chinese Han population by pyrosequencing approach. To our knowledge, pyrosequencing as a quantitative technique was regarded as the golden standard compared with the SNaPshot method in methylation analysis. A total of 38 unrelated male volunteers with ages from 21 to 54 years were successfully analyzed. We fit a linear regression model for age prediction with R 2  = 0.739. We validated the linear regression model with other 17 samples, and the prediction of the mean absolute deviation (MAD) was 4.048 years.